Melatonin promotes secondary hair follicle development of early postnatal cashmere goat and improves cashmere quantity and quality by enhancing antioxidant capacity and suppressing apoptosis. Issue 1 (3rd April 2019) - Yang, Chun‐He; Xu, Jian‐Hai; Ren, Qing‐Chang; Duan, Tao; Mo, Fang; Zhang, Wei
Abstract: Development of secondary hair follicles in early postnatal cashmere goats may be adversely affected by reactive oxygen species which cause oxidative stress. Because melatonin is a potent antioxidant and scavenger of free radicals, this study explored the effects of melatonin on secondary hair follicle development and subsequent cashmere production. It was found that the initiation of new secondary follicles in early postnatal Inner Mongolian cashmere goats of both melatonin‐treated and control goats occurred in the first 10 weeks of age. Melatonin promoted the initiation and maturation of secondary follicles and increased their population. Importantly, the beneficial effect of melatonin on secondary follicle population remained throughout life. As a result, melatonin increased cashmere production and improved its quality in terms of reduced fiber diameter. The mechanisms underlying the role of melatonin on secondary follicle development included the enhancement of activities of antioxidant enzymes, for example, superoxide dismutase and glutathione peroxidase (GSH‐Px), elevated total antioxidant capacity, and upregulated anti‐apoptotic Bcl‐2 expression and downregulated expression of the pro‐apoptotic proteins, Bax and caspase‐3. These results reveal that melatonin serves to promote secondary hair follicle development in early postnatal cashmere goats and expands our understanding of melatonin application in cashmere production. Melatonin treatment led to an increase in both the quantity and quality of cashmere fiber. This increased the textile value of the fibers and provided economic benefit.